2022
DOI: 10.1021/accountsmr.1c00263
|View full text |Cite
|
Sign up to set email alerts
|

Pure Hydrocarbons: An Efficient Molecular Design Strategy for the Next Generation of Host Materials for Phosphorescent Organic Light-Emitting Diodes

Abstract: Fantastic progresses have been made since the discovery of phosphorescent organic light-emitting diodes (PhOLEDs) in 1998. 1 In the emissive layer of a PhOLED, a heavy-metal complex (emitter) is dispersed as a guest in an organic semiconductor (host) in order to harvest both singlet and triplet excitons. This host / guest technique is essential to reach high performance PhOLEDs. Undoubtedly, designing high-efficiency host materials for red, green and blue phosphors has been the main driving force of the field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…2 This achievement has been possible thanks to the development of hundreds of host materials for the last 20 years. [15][16][17][18][19][20] Beside molecular engineering, the architecture of the device itself is of great importance to maximize the conversion of electric energy into luminous energy. [21][22][23] In this context, the most performant PhOLEDs to date are constructed on a multi-layer (ML) stack, which insures a good injection, transport and recombination of holes and electrons in the EML.…”
Section: Introductionmentioning
confidence: 99%
“…2 This achievement has been possible thanks to the development of hundreds of host materials for the last 20 years. [15][16][17][18][19][20] Beside molecular engineering, the architecture of the device itself is of great importance to maximize the conversion of electric energy into luminous energy. [21][22][23] In this context, the most performant PhOLEDs to date are constructed on a multi-layer (ML) stack, which insures a good injection, transport and recombination of holes and electrons in the EML.…”
Section: Introductionmentioning
confidence: 99%
“…28 The applied substitution engineering allows a shift in IP PE and EA PE in relatively narrow ranges. After comparison of the average IP PE and EA PE values of the studied compounds with those of other organic semiconductors, 29 it can be concluded that they can exhibit good hole and electron injecting properties in the appropriate device structure.…”
Section: Resultsmentioning
confidence: 95%
“…5,12,[22][23][24][25] However, whatever the nature of the emitters, achieving high efficiency OLEDs in this range of wavelengths has been one of the most difficult problems to solve for the last twenty years. For example, in phosphorescent OLEDs, which are the most mature technology in the field, very high efficiency red, green and sky-blue devices have been achieved (EQE above 25%) 13,[22][23][24][25][26][27] but deep blue and violet OLEDs are still unattainable. In terms of CIE coordinates, different standards can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%